Quantification and Genotyping of Rotavirus A within Two Wastewater Treatment Processes. Issue 4 (1st February 2016) - Ibrahim, Chourouk; Cherif, Nadia; Hammami, Salah; Pothier, Pierre; Hassen, Abdennaceur
Abstract : The main objectives of this work are: firstly, the study of the circulation of Rotavirus A (RVA) in wastewater sampled from a semi‐industrial wastewater pilot plant. The plant is situated in a residential area of Tunis and irrigated by three different neighboring hospitals; and secondly, the evaluation of the functioning of two wastewater biological treatment procedures (natural lagoons and biodisks) in a semi‐industrial pilot plant for RVA removal using molecular characterization and quantification technology. A total of 102 wastewater samples were collected from two biological treatment processes in a semi‐industrial pilot plant that receives effluents of the sewage system of Tunis City (Tunisia). RVA was detected and quantified in 51 wastewater samples (50%) from the pilot plant. The mean values of viral content (genome copies/μL) obtained in the effluent of the two treatments procedures showed a significant decrease in the prevalence and viral content of RVA observed from upstream to downstream of the studied procedure: natural lagoons and at the exit of the biodisks line. The main G‐type was G8 (35.5%), followed by G9 (16%), G1 (13%), G10 (10%), G3 (13%) and three mixed combined genotypes: G3/G9 (3%), G8/G10 (3%), G9/G8 (6.5%) were identified. The data obtained in this study represent the first documentation in Tunisia dealing with the effectiveness of wastewater biological treatment for the removal of RVA through two biological treatment procedures in a semi‐industrial pilot plant located in the area of Tunis (Tunisia). Abstract : The circulation of Rotavirus A in wastewater is studied and effectiveness of two sewage treatment processes (natural lagoons and biodisks) is evaluated in a semi‐industrial pilot plant. The plant is irrigated and drained by three different neighboring hospitals in the City of Tunis, Tunisia. The study is performed using molecular quantification and characterization techniques.